Monitoring and Evaluation and the Quality of Health-Care Service Delivery in Uganda: A Case of Ntungamo District Local Government. - Nahabwe, Judith (Kabale University., 2024)
The study aimed to examine the impact that monitoring and evaluation have on the quality of healthcare service delivery in Uganda, using Ntungamo District Local Government as a case. Monitoring and evaluation formed a basis for the independent variable and was conceptualized as implementation type of monitoring and evaluation, beneficiary type of monitoring and evaluation, and Social accountability type of monitoring and evaluation. The quality of health care service delivery formed a basis for the dependent variable and was conceptualized into the acceptability of services, accessibility of services, availability of services, and accommodation of users’ needs. Three objectives guided the study and they were formulated to reflect how the three constructs of the independent variable impact the quality of healthcare service delivery. A cross-sectional research design was used where data was collected from 197 respondents and analyzed using Special Package for Social Sciences version 20 to obtain descriptive and inferential statistics. Qualitative data obtained from interviews were presented in narrative form as direct quotations from the respondents. It was established that the implementation type of monitoring and evaluation has a statistically significant positive relationship with the quality of healthcare service delivery as depicted by a correlation coefficient of r=0.308**. Also, beneficiary type of monitoring and evaluation had a statistically significant positive relationship with the quality of healthcare service delivery in Ntungamo District indicated by correlation results r=0.378**. Social accountability type of monitoring and evaluation indicated a statistically significant positive relationship with the quality of healthcare service delivery reflected by r=0.345**. From the findings, the study concluded that monitoring and evaluation have a medium impact on the quality of healthcare service delivery in Uganda but there are other significant factors responsible for the variations in the quality of healthcare service delivery that are not explained by monitoring and evaluation. Therefore, conducting further research on other factors affecting the healthcare service standards like internal controls in healthcare centers would be an asset.